(3CfHGA fLHGA GdCHfGAs - (3eMeO Hf YHO Gddg CHj eMeO Hf eMeO Hf nXnaQ GdUbdj Gdecqj, CHh YHO Gddg, MLI GdOjf,J (B565 (3g` s ((3efadhW s)
(3ChdgG (B:s
(3bGd GHf XaQ Gdeci GdMeO ddg GdeMehO HCbhGd GdegJOjf hCMhGd GdeYJOjf hHYO , agPG cJGH ChOYg ef CfHGA fLHGA GdCHfGA eGgh cTQQI ef VQGe , Hd cbWQI ef QgGe bUOJ Hg JdbjM geI ZdGe s
(3BNQgG (B:s
(3aSeJ geJg Edi GdESJjdGA Ydi eeGdc aGQS hEYGOI CehQge Edi GdfXGe GdeJbOe hWdH Pdc aCOQcg aEf cjheQJ YfO GdaQS gh Chd edhc aEfi bO CJjJ Ydi eG YeOJ dg ai cJGHi gPG ced cJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde eVHhWs
(3cJHgG GdfGSN dfaSgHBNQgG Jedc SfI (B879 (3g`s
(3ai GdeYgO fSNI CNQiI HQbe (B912 (3JGQjN s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdJGQjNs